The student and the ovum: The lack of autonomy and informed consent in trading genes for tuition - Papadimos Alexa T; Papadimos Thomas J (BMC, 2004)
Abstract Rising tuition costs have forced university students to become creative in finding ways to fund their education. Some female university students have decided that ova donation may be an acceptable alternative in which to pay for their tuition. This alternative presents itself because of the insufficient number of ova available for assisted reproduction and emerging stem cell technologies. Young female university students are encouraged by Internet sources and respectable electronic and print media to donate their ova in the cause of assisted reproduction for monetary compensation. While university students generally exhibit autonomy, the constraining influence of their financial predicament compromises the elements of informed consent (voluntariness, competence, capacity, understanding, and disclosure) as to their making an autonomous decision in regard to egg donation. Thus, any moral possibility of giving informed consent is negated. Informed consent can only occur through autonomy. A female university student in need of financial resources to pay for her education cannot make an autonomous choice to trade her genes for tuition. Donated ova are not only needed for assisted reproduction, but for stem cell technologies. While the long-term health of women who donate their ova is of concern (a potential risk of cancer after long term use of ovulation induction), of equal concern is the possibility of a growth in the trade of ova targeting third world and Eastern European women where the precedence for autonomy and informed consent is not well established.